From cheap entertainment to expensive pleasure: Cinema-going habits and motivations of young people in Türkiye - Nermin Küçüksönmez; Abdullah Koçak; Nuh Akçakaya (PLoS ONE, 2026)
This study examines the cinema-going habits and motivations of university students in Türkiye from a class-based perspective. This study addresses a gap in the literature by examining cinema-going motivations in Türkiye through a class-based perspective. Participants (N = 1183) were recruited using a convenience sampling method from 12 universities across the NUTS 1 regions of Türkiye. This quantitative study employed three measurement tools to assess participants’ sociodemographic and socioeconomic characteristics, cinema-going habits, and motivations. The findings suggest that socialization was the most prominent factor associated with cinema-going motivation among participants. Cinema was not widely perceived by participants as a means of coping with loneliness, but rather as an activity associated with social interaction. The technical capabilities of cinema also emerged as an important factor associated with cinema attendance. While individuals reported different motivations, class-related differences were associated with variations in cinema-going behaviors within this sample. Participants with higher socioeconomic indicators tended to report higher levels of cinema attendance, whereas those with lower socioeconomic indicators reported lower levels of attendance. Given the convenience sampling design and the student-only composition of the sample, the findings should be interpreted with caution and should not be generalized beyond the study population.